2016
DOI: 10.1016/j.jcis.2016.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Structural perturbation of a dipalmitoylphosphatidylcholine (DPPC) bilayer by warfarin and its bolaamphiphilic analogue: A molecular dynamics study

Abstract: Compounds with nominally similar biological activity may exhibit differential toxicity due to differences in their interactions with cell membranes. Many pharmaceutical compounds are amphiphilic and can be taken up by phospholipid bilayers, interacting strongly with the lipid-aqueous interface whether or not subsequent permeation through the bilayer is possible. Bolaamphiphilic compounds, which possess two hydrophilic ends and a hydrophobic linker, can likewise undergo spontaneous uptake by bilayers. While mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Likewise, BDF-poisoned bobcats (Lynx rufus) residing in southern California die predominantly from severe systemic inflammation elicited by parasite mites whereas BDF-poisoned mountain lions (Puma concolor) in the same area die from massive internal bleeding (Fraser et al, 2018;Serieys et al, 2018). In addition, we found that exposure of primary neuronal cells to BDF induced mitochondrial dysfunction and cell death (Marangoni et al, 2016) and that BDF (and other superwarfarins but not warfarin) can intercalate into and disrupt cell membranes (Ayee et al, 2016), which could dysregulate cell function and induce cell death. Although the mechanism(s) underlying these disparate toxic effects are uncertain, the presence of distinct BDF isomers in racemic BDF may play a role.…”
Section: Discussionmentioning
confidence: 79%
“…Likewise, BDF-poisoned bobcats (Lynx rufus) residing in southern California die predominantly from severe systemic inflammation elicited by parasite mites whereas BDF-poisoned mountain lions (Puma concolor) in the same area die from massive internal bleeding (Fraser et al, 2018;Serieys et al, 2018). In addition, we found that exposure of primary neuronal cells to BDF induced mitochondrial dysfunction and cell death (Marangoni et al, 2016) and that BDF (and other superwarfarins but not warfarin) can intercalate into and disrupt cell membranes (Ayee et al, 2016), which could dysregulate cell function and induce cell death. Although the mechanism(s) underlying these disparate toxic effects are uncertain, the presence of distinct BDF isomers in racemic BDF may play a role.…”
Section: Discussionmentioning
confidence: 79%
“…2) [50]. Another CG study found that membrane partitioning of toxic anticoagulant brodifacoum causes bilayer thinning and permeabilization that promotes lipid flip-flop, which potentially plays a role in triggering cell death [51]. In addition, atomistic umbrella sampling simulations on the flip-flop of PS showed that membrane oxidation decreases the energy barrier for translocation [52].…”
Section: Protein-mediated Lipid Flip-flop Across the Bilayer As A Majmentioning
confidence: 99%
“…The second approach is to use coarse‐grained molecular dynamic simulations of BDF . While BDF is a highly lipophilic compound, its molecular structure possesses regions of polarity, such as the 4‐hydroxycoumarin moiety that BDF shares with warfarin.…”
Section: Novel Molecular Actions Of Superwarfarinsmentioning
confidence: 99%
“…The second approach is to use coarse-grained molecular dynamic simulations of BDF. 69 While BDF is a highly lipophilic compound, its molecular structure possesses regions of polarity, such as the 4-hydroxycoumarin moiety that BDF shares with warfarin. The compound is also a weak acid (pKa 5) and would be expected to adopt a predominately deprotonated, anionic form at physiological pH.…”
Section: Novel Molecular Actions Of Superwarfarinsmentioning
confidence: 99%